A method for electrochemically synthesizing crystalline iron silicate minerals and simultaneously immobilizing uranium in wastewater
Patent Information
- Application Number
- CN202611222570.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-13
AI Technical Summary
然而,在传统化学沉淀体系中,硅酸盐通常吸附于铁氧化物或铁氢氧化物前驱体表面,并可能抑制铁矿物由非晶相向晶态相转化,导致所得产物多为无序或低结晶度的铁硅沉淀物,该类产物对铀的固定主要依赖表面吸附、共沉淀或物理包埋,难以实现铀在晶态铁硅酸盐矿物结构中的有效限域固定
本发明通过向含铀废水中加入水溶性硅酸盐,以含铁电极为阳极施加特定电流密度进行电化学矿化反应,使阳极溶出的铁物种与硅酸盐反应生成铁硅酸盐矿物,并在矿物形成过程中将铀同步固定于矿物晶格中,实现铀的高效去除与稳固晶格固定,铀去除率达99%以上,所得矿化产物在酸性条件下铀浸出率最低为2.9%。本发明在所述电化学矿化反应的过程中,利用电场诱导离子迁移及电极界面微环境调控,使硅酸盐转变为参与Fe-O-Si骨架构筑的活性结构单元,通过协同控制硅酸盐浓度、电流密度、反应体系pH值及反应时间,使铁物种的释放速率与硅物种的水解、缩聚速率相匹配,并使体系中的硅物种与铁物种处于有利于形成含铀铁硅酸盐矿物的特定匹配区间,铁阳极释放的铁物种能够与硅物种发生协同水解、缩聚和有序组装,促进形成以Fe-O-Si连接为骨架特征、具有纳米晶结构域的含铀铁硅酸盐矿物,铀在矿化过程中与所形成的Fe-O-Si骨架形成结构耦合固定,通过U-O-Si和/或U-O-Fe键合实现铀在铁硅酸盐骨架中的结构嵌入,从而提高长期固定能力。
Smart Images

Figure CN122907407A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of radioactive wastewater treatment, environmental pollution remediation, and electrochemical mineralization, specifically to a method for electrochemically synthesizing crystalline iron silicate minerals and simultaneously fixing uranium in wastewater. Background Technology
[0002] Mining, uranium smelting, nuclear fuel cycle and tailings dam operation generate a certain amount of uranium-containing wastewater. Uranium, especially hexavalent uranium (U(VI)), usually has high solubility and mobility in the aquatic environment, and has radiotoxicity and chemical toxicity. If not handled properly, it may cause long-term potential harm to groundwater, soil ecosystems and human health.
[0003] Existing technologies for treating uranium-containing wastewater mainly include adsorption, chemical precipitation, coprecipitation, reductive deposition, ion exchange, and membrane separation. Among these, adsorption and precipitation technologies are widely studied and applied due to their relatively simple operation and low cost. However, these methods typically achieve the transfer of uranium from the aqueous phase to the solid phase, with uranium existing in the solid phase primarily through surface adsorption, coordination bonding, physical embedding, or coprecipitation. Under environmental disturbances such as acidic leaching, changes in redox conditions, competition for complexing agents, or microbial activity, the fixed uranium still carries the risk of re-release, easily leading to secondary pollution. Therefore, improving the structural stability and leaching resistance of uranium-containing solid products is crucial for achieving long-term stable uranium fixation.
[0004] Silicate minerals possess strong Si-O bonds and a stable silicon-oxygen framework, which enhances their structural stability and has the potential to contain or fix radionuclides. Introducing silicate components into iron-based mineral systems to form iron-silicate mineral structures is an important way to improve the stability of uranium fixation. However, in traditional chemical precipitation systems, silicates are usually adsorbed on the surface of iron oxides or iron hydroxide precursors and may inhibit the transformation of iron minerals from amorphous to crystalline phases. This results in products that are mostly disordered or low-crystallinity iron-silicon precipitates. The fixation of uranium in these products mainly relies on surface adsorption, co-precipitation, or physical embedding, making it difficult to achieve effective confined fixation of uranium in crystalline iron-silicate mineral structures. Summary of the Invention
[0005] In view of this, the purpose of this invention is to provide a method for electrochemically synthesizing crystalline iron silicate minerals and simultaneously immobilizing uranium in wastewater. This invention involves adding water-soluble silicates to uranium-containing wastewater, applying a specific current density using an iron-containing electrode as the anode to conduct an electrochemical mineralization reaction. The iron species dissolved at the anode react with the silicates to form iron silicate minerals, and uranium is simultaneously immobilized in the mineral lattice during the mineralization process. This achieves highly efficient uranium removal and stable lattice fixation, with a uranium removal rate exceeding 99%. The resulting mineralization product exhibits a minimum uranium leaching rate of 2.9% under acidic conditions.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for electrochemically synthesizing crystalline iron silicate minerals and simultaneously fixing uranium in wastewater, comprising the following steps: Water-soluble silicates are added to the uranium-containing water body to be treated to obtain a uranium-containing silicate mixture; An electrochemical mineralization reaction was carried out using the uranium-containing silicate mixture as the electrolyte, an iron-containing electrode as the anode, and a conductive inert electrode as the cathode to obtain uranium-containing crystalline iron silicate minerals and treated water. The current density of the electrochemical mineralization reaction is 2~3 mA / cm². 2 ; The concentration of silicon in the uranium-containing silicate mixture is 2-5 mmol / L, calculated as Si. The pH value of the uranium-containing silicate mixture is 2.0~4.0.
[0007] Preferably, the electrochemical mineralization reaction has a reaction time of 60-240 min and a reaction temperature of 15-35℃.
[0008] Preferably, the water-soluble silicate includes one or more of sodium silicate, sodium metasilicate, potassium silicate, and potassium metasilicate.
[0009] Preferably, the concentration of uranium in the uranium-containing water body to be treated is 1~20 mg / L.
[0010] Preferably, the iron-containing electrode includes a pure iron electrode, an iron alloy electrode, or a zero-valent iron loaded electrode. The pure iron electrode includes one or more of iron plates, iron sheets, iron rods, iron mesh, iron wire, iron filings, and foamed iron. The iron alloy electrode is made of cast iron or stainless steel. The conductive inert electrode includes a carbon-based electrode, a titanium-based electrode, or a platinum electrode. The carbon-based electrode includes one or more of graphite, carbon rods, carbon felt, carbon cloth, and glassy carbon. The titanium-based electrode includes a titanium plate or titanium mesh. The platinum electrode includes a platinum sheet or platinum mesh.
[0011] Preferably, the distance between the iron-containing electrode and the conductive inert electrode is 1~15cm.
[0012] Preferably, after the electrochemical mineralization reaction is completed, solid-liquid separation and vacuum drying are performed. The vacuum drying temperature is 50~60℃ and the vacuum degree is -0.1~-0.2MPa.
[0013] Preferably, the uranium-containing water to be treated includes one or more of uranium-containing waste liquid, uranium-containing silicate waste liquid, and uranium-containing mine wastewater.
[0014] The present invention also provides uranium-containing crystalline iron silicate minerals obtained by the method described in the above technical solution.
[0015] Preferably, the morphology of the uranium-containing crystalline iron silicate mineral includes one or more of the following: layered, chain-like, platy, flocculent, spherical, and microcrystalline aggregates.
[0016] This invention provides a method for electrochemically synthesizing crystalline iron silicate minerals and simultaneously fixing uranium in wastewater, comprising the following steps: Water-soluble silicates are added to the uranium-containing water body to be treated to obtain a uranium-containing silicate mixture; An electrochemical mineralization reaction was carried out using the uranium-containing silicate mixture as the electrolyte, an iron-containing electrode as the anode, and a conductive inert electrode as the cathode to obtain uranium-containing crystalline iron silicate minerals and treated water. The current density of the electrochemical mineralization reaction is 2~3 mA / cm². 2 ; The concentration of silicon in the uranium-containing silicate mixture is 2-5 mmol / L, calculated as Si. The pH value of the uranium-containing silicate mixture is 2.0~4.0.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention involves adding water-soluble silicates to uranium-containing wastewater and applying a specific current density using an iron-containing electrode as the anode to conduct an electrochemical mineralization reaction. This allows the iron species dissolved at the anode to react with the silicates to form iron silicate minerals. During the mineral formation process, uranium is simultaneously fixed in the mineral lattice, achieving efficient uranium removal and stable lattice fixation. The uranium removal rate reaches over 99%, and the uranium leaching rate of the resulting mineralized product is as low as 2.9% under acidic conditions. In the electrochemical mineralization process described in this invention, the electric field induces ion migration and the electrode interface microenvironment is controlled to transform silicates into active structural units that participate in the construction of the Fe-O-Si framework. By synergistically controlling the silicate concentration, current density, pH value of the reaction system, and reaction time, the release rate of iron species is matched with the hydrolysis and condensation rate of silicon species, and the silicon species and iron species in the system are placed in a specific matching range that is conducive to the formation of uranium-containing iron silicate minerals. The iron species released from the iron anode can undergo synergistic hydrolysis, condensation, and ordered assembly with silicon species, promoting the formation of uranium-containing iron silicate minerals with Fe-O-Si linkages as the framework characteristics and nanocrystalline structural domains. Uranium forms a structural coupling and fixation with the Fe-O-Si framework during the mineralization process, and the structural embedding of uranium in the iron silicate framework is achieved through UO-Si and / or UO-Fe bonding, thereby improving the long-term fixation ability.
[0018] Furthermore, the process of this invention is simple, the reaction conditions are mild, and there is no need for high temperature, high pressure, hydrothermal treatment or long-term aging. It can rapidly form nanocrystalline Fe-O-Si mineral frameworks through electrochemical mineralization at room temperature and pressure, which is suitable for continuous and large-scale applications. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the electrochemical mineralization reaction device in an embodiment of the present invention; Figure 2 The XRD patterns of Example 1 and Comparative Example 1 are shown below. Figure 3 In the image, a is a morphology image of the sample in Example 1, b is an HRTEM image of the sample in Example 1, c is a SAED image of the sample in Example 1, d is a morphology image of the sample in Comparative Example 1, e is an HRTEM image of the sample in Comparative Example 1, and f is a SAED image of the sample in Comparative Example 1. Figure 4 This is a comparison chart of uranium removal rate and acid leaching release rate of the samples in Example 1 and Comparative Examples 1-2; Figure 5 The graph shows the uranium removal rate and acid leaching release rate of the samples at different pH values in Example 2. Figure 6 The graph shows the uranium removal rate and acid leaching release rate of the samples under different current densities in Example 3. Figure 7 The XRD patterns of the samples under different current densities in Example 3 are shown. Figure 8 The graph shows the uranium removal rate and acid leaching release rate of the samples at different silicate concentrations in Example 4. Figure 9 The Si / (Si+Fe) molar ratio of the samples at different silicate concentrations in Example 4; Figure 10 The Raman spectrum of the sample in Example 1; Figure 11 The FTIR spectrum of the sample in Example 1; Figure 12 The elemental distribution diagram of Fe, Si, O and U in the sample of Example 1 is shown. Figure 13 The XPS spectrum and Fe and U valence state analysis diagrams of the sample in Example 1 are shown. Figure 14 This is a graph showing the EXAFS fitting results of the sample in Example 1; Figure 15 The graph shows the removal rate and leaching rate of uranium and other metal ions in the actual uranium-containing wastewater treatment in Example 5. Detailed Implementation
[0020] This invention provides a method for electrochemically synthesizing crystalline iron silicate minerals and simultaneously fixing uranium in wastewater, comprising the following steps: Water-soluble silicates are added to the uranium-containing water body to be treated to obtain a uranium-containing silicate mixture; An electrochemical mineralization reaction was carried out using the uranium-containing silicate mixture as the electrolyte, an iron-containing electrode as the anode, and a conductive inert electrode as the cathode to obtain uranium-containing crystalline iron silicate minerals and treated water. The current density of the electrochemical mineralization reaction is 2~3 mA / cm². 2 ; The concentration of silicon in the uranium-containing silicate mixture is 2-5 mmol / L, calculated as Si. The pH value of the uranium-containing silicate mixture is 2.0~4.0.
[0021] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0022] In this invention, the water-soluble silicate preferably includes one or more of sodium silicate, sodium metasilicate, potassium silicate and potassium metasilicate. The concentration of silicon in the uranium-containing silicate mixture is preferably 2 to 5 mmol / L, specifically 3 or 4 mmol / L, calculated as Si.
[0023] In this invention, the uranium in the uranium-containing wastewater preferably includes hexavalent uranium, which preferably exists in one or more forms selected from uranyl ions, uranyl carbonate complexes, uranyl sulfate complexes, uranyl nitrate complexes, and uranyl chloride complexes. The concentration of uranium in the uranium-containing water to be treated is preferably 1~20 mg / L, specifically 5, 8, 10, 12, 16, or 18 mg / L. This interacts with the current density of the subsequent electrochemical mineralization reaction, allowing the iron species released from the iron anode to undergo synergistic hydrolysis, condensation, and ordered assembly with silicon species, promoting the formation of uranium-containing iron silicate minerals with Fe-O-Si linkages as the framework and nanocrystalline structural domains. During the mineralization process, uranium forms a structural coupling and fixation with the formed Fe-O-Si framework.
[0024] In this invention, the uranium-containing water to be treated preferably includes one or more of uranium-containing waste liquid, uranium-containing silicate waste liquid, and uranium-containing mine wastewater.
[0025] In this invention, the pH value of the uranium-containing silicate mixture is 2.0 to 4.0, more preferably 2.5, and the pH value of the uranium-containing silicate mixture is preferably adjusted with dilute sulfuric acid.
[0026] After obtaining the uranium-containing silicate mixture, the present invention uses the uranium-containing silicate mixture as the electrolyte, an iron-containing electrode as the anode, and a conductive inert electrode as the cathode to carry out an electrochemical mineralization reaction to obtain uranium-containing crystalline iron silicate minerals and treated water.
[0027] In this invention, the iron-containing electrode preferably comprises a pure iron electrode, a ferroalloy electrode, or a zero-valent iron-loaded electrode. The pure iron electrode preferably comprises one or more of iron plates, iron sheets, iron rods, iron mesh, iron wire, iron filings, and foamed iron. The ferroalloy electrode is preferably made of cast iron or stainless steel. The conductive inert electrode preferably comprises a carbon-based electrode, a titanium-based electrode, or a platinum electrode. The carbon-based electrode preferably comprises one or more of graphite, carbon rods, carbon felt, carbon cloth, and glassy carbon. The titanium-based electrode preferably comprises a titanium plate or titanium mesh. The platinum electrode preferably comprises a platinum sheet or platinum mesh. The iron-containing electrode acts as a sacrificial anode, releasing Fe under electrochemical action. 2+ This provides an iron source for the in-situ construction of crystalline iron silicate minerals. The conductive material serves as a cathode to form an electrochemical circuit, thereby promoting the hydrolysis, polymerization, and mineralization reactions of iron species and silicates.
[0028] In this invention, the distance between the iron-containing electrode and the conductive inert electrode is preferably 1 to 15 cm, specifically 5, 8, 10, 12 or 14 cm.
[0029] In this invention, the electrochemical mineralization reaction is preferably carried out in a batch electrolytic reactor or a continuous flow electrolytic reactor.
[0030] In this invention, a constant current is preferably applied to carry out the electrochemical mineralization reaction, and the current density of the electrochemical mineralization reaction is 2~3 mA / cm². 2 Specifically, it can be 2.2, 2.5, 2.8, or 3.0 mA / cm. 2 When the current density is too low, the release rate of iron species is insufficient, making it difficult to effectively match the condensation process of silicon species. This is not conducive to the formation of the target uranium-containing iron silicate minerals. The resulting uranium-containing iron-silicon solid phase is mainly amorphous or iron sulfate solid phase. Uranium still faces the risk of secondary release under acidic or environmental disturbance conditions. When the current density is too high, the release of iron species is too fast, which easily leads to hydrolysis, oxidation, and aggregation, forming iron oxide or iron oxide (hydride) solid phases. This is not conducive to the orderly construction of the Fe-O-Si framework. This invention controls the current density within the range that is conducive to the continuous release of iron from the iron anode, and controls the concentration of silicon in the silicate and the amount of iron anode dissolution within a specific matching range. This allows iron species, silicon species, and uranium species to synergistically form a nanocrystalline uranium-containing iron-silicon mineralization phase during the electrochemical reaction, thereby improving the structural fixation ability and leaching resistance of uranium.
[0031] In this invention, the reaction time of the electrochemical mineralization reaction is preferably 60-240 min, specifically 90, 120, 150, 180 or 210 min, and the reaction temperature of the electrochemical mineralization reaction is preferably 15-35℃, specifically 18, 20, 25 or 30℃. Under the influence of the local redox environment and pH environment formed by the electrochemical reaction, the iron species in the iron-containing electrode undergo hydrolysis, polymerization and mineralization reactions with silicates, generating crystalline iron silicate minerals in situ. During the formation of the crystalline iron silicate minerals, uranium in the uranium-containing wastewater enters the solid phase of the newly formed mineral through adsorption, co-precipitation, surface complexation, structural confinement or lattice doping, thereby achieving simultaneous removal and stable fixation of uranium in the wastewater.
[0032] This invention, during the electrochemical reaction process, synergistically controls silicate concentration, current density, pH value of the reaction system, and reaction time to create a local reaction environment at the electrode interface and its adjacent regions that is conducive to the hydrolysis and transformation of iron species, the condensation of silicon species, and the simultaneous fixation of uranium species. This allows iron, silicon, and uranium species to gradually accumulate in local areas and form a uranium-containing iron-silicon mineralized solid phase, promoting the participation of silicon species in the formation and assembly of Fe-O-Si structural units, thereby regulating the composition and structural characteristics of the uranium-containing iron-silicon solid phase. Compared to the disordered or low-crystallinity iron-silicon coprecipitates that easily form when the ratio of silicate to iron species is unsuitable, under suitable conditions of silicon-iron ratio, current density, and reaction time, it is beneficial to form a uranium-containing iron-silicon mineralized solid phase with nanocrystalline structural domains. During the mineralization process, uranium species can be captured and fixed through coprecipitation, local structural confinement, and structural association with the Fe-O-Si framework. Some uranium has a structural coupling relationship with the iron-silicon framework, achieving structural embedding of uranium in the iron silicate framework through UO-Si and / or UO-Fe bonding, thereby improving long-term fixation capability.
[0033] This invention utilizes electric field-induced ion migration and electrode interface microenvironment regulation to transform silicates into active structural units that participate in the construction of the Fe-O-Si framework. This invention not only fixes uranium through Fe(II)-mediated reduction, but also achieves structural embedding of uranium in the iron silicate framework through UO-Si and / or UO-Fe bonding, thereby improving long-term fixation capability.
[0034] In this invention, after the electrochemical mineralization reaction is completed, solid-liquid separation is preferably performed to obtain the uranium-containing crystalline iron silicate mineral and the treated water.
[0035] In this invention, the solid-liquid separation preferably includes one or more of the following: natural sedimentation, filtration, centrifugation, membrane separation, pressure filtration, and magnetic separation.
[0036] In this invention, vacuum drying is preferably performed after the solid-liquid separation is completed. The vacuum drying conditions preferably include: a temperature of 50~60℃ and a vacuum degree of -0.1~-0.2MPa. The vacuum drying is used to gently remove adsorbed water, pore water and some free water from the solid phase, reducing the disturbance of the post-processing process to the formed microcrystalline Fe-O-Si framework structure and the uranium fixation state.
[0037] The present invention also provides uranium-containing crystalline iron silicate minerals obtained by the method described in the above technical solution.
[0038] In this invention, the morphology of the uranium-containing crystalline iron silicate mineral preferably includes one or more of the following: layered, chain-like, platy, flocculent, spherical, and microcrystalline aggregates.
[0039] In this invention, the uranium-containing crystalline iron silicate mineral preferably includes iron silicate minerals containing Fe-O-Si structural units. The iron silicate mineral can serve as a mineral host for uranium and fix uranium through surface complexation, co-precipitation, structural confinement, or lattice doping.
[0040] In this invention, the iron silicate mineralization product preferably comprises an iron silicate microcrystalline phase having Fe-O-Si structural units, and further comprises Fe6Fe3O3(Si6O 17 )(OH)5 is a microcrystalline phase of iron silicate with a similar structure.
[0041] Compared to the amorphous or low-crystallinity iron-silicon oxide solid phases in existing technologies, the uranium-containing crystalline iron-silicon mineral solid phase obtained by this invention exhibits stronger structural fixation characteristics in uranium, thereby improving its resistance to leaching and reducing the risk of secondary uranium release under acidic conditions or environmental disturbances. Examples demonstrate that the method of this invention can be applied to practical uranium-containing wastewater treatment, achieving effective uranium removal while obtaining a uranium-containing iron-silicon mineralized solid phase with a low uranium leaching rate, demonstrating significant practical application value.
[0042] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0043] Figure 1 This is a schematic diagram of the electrochemical mineralization reaction apparatus used in an embodiment of the present invention, as shown below. Figure 1 As shown, the anode of the device is made of iron sheet and the cathode is made of graphite. Under the action of current, the iron at the anode corrodes and releases ferrous ions, which combine with silicate ions in the solution to generate iron silicate mineralization products at the cathode and the bottom of the device, thereby achieving synchronous fixation of uranium.
[0044] Example 1 Take 500 mL of uranium-containing simulated wastewater with an initial U(VI) concentration of 10 mg / L. Add sodium silicate to the uranium-containing simulated wastewater to make the silicate concentration in the system 3 mmol / L (calculated as Si). Adjust the initial pH of the solution to 2.5 with dilute sulfuric acid to obtain a uranium-containing silicate mixture. Using an iron sheet as the anode and graphite as the cathode, the anode and cathode were placed in the aforementioned uranium-containing silicate mixture. The distance between the two electrodes was controlled at 13 cm. Under normal pressure conditions at room temperature (25°C), the current was applied at 2 mA / cm. 2 The constant current electrolysis reaction was carried out at a current density of 180 min. After the reaction was completed, the reaction system was allowed to settle, the supernatant and the bottom sediment were separated, the bottom sediment was collected, washed with deionized water, and dried under vacuum to obtain the uranium-containing iron silicate mineralization product, denoted as E-3mMSi. The structure of the obtained uranium-containing iron silicate mineralization product was characterized, and the results showed that the product has a nanocrystalline Fe-O-Si framework structure. Figure 2 The XRD patterns of Example 1 and Comparative Example 1 are shown; from Figure 2 It can be seen that Fe6Fe3O3(Si6O 17 The characteristic diffraction peaks of (OH)5 or iron silicate crystal phases with similar structures are estimated by the Scherrer equation to be about 37 nm in grain size. Figure 3 Image a is a morphology image of the sample from Example 1, image b is an HR-TEM image of the sample from Example 1, image c is a SAED image of the sample from Example 1, image d is a morphology image of the sample from Comparative Example 1, image e is an HR-TEM image of the sample from Comparative Example 1, and image f is a SAED image of the sample from Comparative Example 1; from Figure 3 Clear lattice fringes can be observed in b. Figure 3 The presence of diffraction rings in c indicates that the obtained product has crystalline structural domains, suggesting that the electrochemical process can induce the formation of crystalline or nanocrystalline iron silicate minerals under ambient temperature and pressure conditions.
[0045] Figure 4 The graph shows a comparison of the uranium removal rate and acid leaching release rate of the products obtained in Example 1 and Comparative Examples 1-2. It can be seen that the U(VI) removal rate in the uranium-containing simulated wastewater is 99.7%. The uranium-containing iron silicate mineralization product was subjected to a leaching test under simulated acid rain conditions of dilute sulfuric acid with a pH of 5, an oscillation rate of 120 r / min, and a leaching time of 3 h. The uranium leaching rate was 2.9%, and the iron release rate was 8.0%. This indicates that the iron silicate mineralization product obtained in this example can be rapidly formed at room temperature and pressure, and uranium in the wastewater is removed and fixed simultaneously during the formation process. The resulting solid has good anti-leaching stability against uranium.
[0046] Figure 10 The image shows the Raman spectrum of the sample in Example 1. The E-3mMSi product shows characteristic signals related to Si-O bending vibration, Fe-O stretching vibration and Fe-O-Si bridging vibration, indicating that iron species and silicate species are coupled during the reaction and form an iron silicate framework structure.
[0047] Figure 11 The image shows the FT-IR spectrum of the sample in Example 1. The product contains Si-O-Si, Fe-O, and Fe-O-Si bond-related absorption peaks, indicating that the Fe-O units are effectively connected to the Si-O units.
[0048] Figure 12 The image shows the elemental distribution of Fe, Si, O, and U in the sample of Example 1. Fe, Si, O, and U elements are uniformly distributed in the product, with the distribution areas of Fe, Si, and O elements highly overlapping. U element shows obvious co-location distribution with the iron silicate matrix, indicating that uranium is fixed synchronously with the iron silicate product during the electrochemical mineralization process, rather than forming a uranium phase separately or only adsorbing on the product surface.
[0049] Figure 13 The XPS spectrum and Fe and U valence state analysis diagrams of the sample in Example 1 are shown. Fe(II) and Fe(III) coexist in the product, accompanied by partial U(VI) reduction, indicating that the iron-containing active species generated during the electrochemical reaction are beneficial to the reduction and fixation of uranium.
[0050] Figure 14 The image shows the EXAFS fitting results of the sample in Example 1. The E-3mMSi product exhibits UO-Si and UO-Fe bonding characteristics, indicating that uranium is not merely adsorbed on the surface but is stably fixed through structural coupling with the iron silicate framework. These characterization results demonstrate that the present invention, through electrochemically induced synergistic mineralization of iron species and silicates, can form uranium-containing iron silicate mineralization products with Fe-O-Si framework, iron silicate interface structure, and uranium structural fixation characteristics, thereby improving uranium removal efficiency and acid leaching resistance. The degree of crystallinity of the uranium-containing iron silicate mineralization product is not solely determined by silicate concentration. Even within the specified silicate concentration range, the resulting product primarily exhibits an amorphous or low-crystallinity iron silicate solid phase. This is because silicate concentration is only one factor affecting the mineralization process; the iron species release rate, reaction system pH, current density, and the matching relationship between silicon and iron species all influence the formation, condensation, and ordered assembly of Fe-O-Si structural units.
[0051] Example 2 Similar to Example 1, except that the silicate concentration was 5 mmol / L (calculated as Si), and the initial pH of the simulated uranium-containing wastewater was adjusted to 2.5, 3.0, 4.0, 5.0, and 7.0 respectively using dilute sulfuric acid or dilute alkali solution.
[0052] Figure 5 The figures show the uranium removal rate and acid leaching release of the samples at different pH values in Example 2. Under the condition of silicate concentration of 5 mmol / L, pH value has a significant impact on the U(VI) removal rate and the leaching resistance stability of the obtained mineralized products. Acidic conditions are more conducive to U(VI) removal and stable fixation. When the pH value increases from 2.5 to 7.0, the U(VI) removal rate decreases from 99.1% to 81.1%. When acid leaching is carried out under the simulated acid rain conditions of dilute sulfuric acid at pH value of 5, the uranium leaching rate increases from 8.0% to 14.1%. The above results indicate that under lower initial pH conditions, iron anodes are more likely to dissolve and form Fe(II) or Fe(III) species, which is conducive to the hydrolysis and polymerization of silicates and the formation of iron silicate mineral phases, and promotes uranium participation in mineral growth or fixation in the Fe-O-Si framework structure. Among them, the pH value of 2.5~4.0 has better uranium removal and fixation effect, especially when the pH value is 2.5~3.0, the resulting mineralized products show better uranium removal performance and acid leaching resistance.
[0053] Example 3 Same as Example 1, except that the silicate concentration (Si) was 5 mmol / L, and the current densities were 1, 2, 3, 4, and 6 mA / cm². 2 .
[0054] Figure 6 The graphs show the uranium removal rate and acid leaching release of the samples at different current densities in Example 3; when the current density is 1 mA / cm². 2 At that time, the release rate of iron species in the system was low, the iron silicate mineralization reaction was incomplete, and amorphous minerals or iron sulfate minerals were formed. The U(VI) removal rate was 85.8%, and the uranium leaching rate was 67.5% under acid leaching conditions (pH value of 5, oscillation rate of 120 r / min, leaching time of 3 h). When the current density increased to 2 mA / cm 2 At this time, the iron anode dissolution rate was well matched with the silicate hydrolysis and polymerization process, which was conducive to the formation of more stable iron silicate mineral products. The U(VI) removal rate increased to 99.5%, and the uranium leaching rate was significantly reduced to 8.0% under acid leaching conditions (pH value of 5, oscillation rate of 120 r / min, leaching time of 3 h). The current density was further increased to 3, 4 and 6 mA / cm. 2 At that time, the improvement in U(VI) removal rate and the acid leaching resistance of the resulting mineralized products was limited.
[0055] Figure 7The XRD patterns of samples under different current densities in Example 3 are shown. Under high current density conditions, the iron anode dissolves rapidly, resulting in an excess of iron species relative to silicates in the system. This leads to an imbalance in the Fe / Si ratio, and the silicates are insufficient to fully participate in the construction of the Fe-O-Si framework. The resulting product is dominated by iron oxide crystal phases rather than iron silicate mineralization phases, and its acid leaching and fixation effect on uranium is weaker than that at 2 mA / cm². 2 The results show that, under the same or similar silicate concentrations, the current density still significantly affects the phase composition of the product. Only when the iron anode dissolution rate matches the rate at which silicate participates in the Fe-O-Si framework can the target microcrystalline iron silicate mineralization phase be formed. Therefore, silicate concentration is not the only parameter that determines the crystallization and uranium structure fixation of the product.
[0056] Example 4 Similar to Example 1, except that the silicate concentrations in the system, expressed as Si, are 1, 3, 5, 7 and 10 mmol / L.
[0057] Figure 8 The graph shows the uranium removal rate and acid leaching release rate of the samples under different silicate concentrations in Example 4. Silicate concentration has a significant impact on U(VI) removal and stable fixation. With increasing silicate concentration, the U(VI) removal rate first increases and then decreases, while the acid leaching uranium leaching rate first decreases and then increases. When the silicate concentration is 1 mmol / L, the U(VI) removal rate is 98.8%, but the acid leaching uranium leaching rate (acid leaching conditions: pH=5, oscillation rate 120 r / min, leaching time 3 h) reaches 28.8%, indicating that insufficient silicate concentration makes it difficult for the Fe-O-Si framework to form sufficiently, resulting in a weaker product stability. When the silicate concentration increases to 3 mmol / L, the U(VI) removal rate increases to 99.7%, and the acid leaching uranium leaching rate (acid leaching conditions: pH=5, oscillation rate 120 r / min, leaching time 3 h) reaches 28.8%. The uranium removal rate (U(VI)) decreased to 2.9% when the silicate concentration was 5 mmol / L, showing good uranium removal and stabilization effects. When the silicate concentration was 5 mmol / L, the U(VI) removal rate remained at 99.1%, and the uranium leaching rate (acid leaching conditions: pH=5, oscillation rate of 120 r / min, leaching time of 3 h) was 8.0%, still showing good uranium stabilization. After further increasing the silicate concentration, both the uranium removal rate and uranium stabilization decreased. When the silicate concentration was 10 mmol / L, the U(VI) removal rate decreased to 84.8%, and the uranium leaching rate (acid leaching conditions: pH=5, oscillation rate of 120 r / min, leaching time of 3 h) increased to 30.6%. This indicates that excessive silicate may lead to silicon enrichment, phase separation, or oligomeric silicate residue in the system, weakening the orderly assembly of the iron silicate framework, which is not conducive to the stable fixation of uranium.
[0058] Figure 9 The molar ratio of Si / (Si+Fe) in the samples with different silicate concentrations in Example 4 is given. When the molar ratio of Si / (Si+Fe) in the product is 30~37.5%, the mineralized product usually exhibits a lower uranium leaching rate and higher structural stability.
[0059] Example 5 A continuous-flow electrochemical mineralization system was used to treat actual uranium-containing wastewater (uranium concentration of 8.8 mg / L). An appropriate amount of silicate (3 mmol / L) was added to the continuous-flow system as a mineralization control component, and an iron sheet was used as the anode and a graphite sheet as the cathode (current density of 2 mA / cm²). 2 Electrochemically induced iron silicate mineralization was performed under continuous influent and effluent conditions (pH 2.5, temperature 25℃, electrode spacing 14cm). During operation, a sampling period of 3 hours was used to measure the U(VI) concentration in the effluent for each period, and the uranium removal effect over 24 hours of continuous operation was statistically analyzed. Simultaneously, considering the gradual deposition and accumulation of solid mineralization products within the reactor during continuous operation, to evaluate the acid leaching stability of newly generated mineralization products under actual operating conditions, solid samples obtained after 3 hours of operation were selected. After solid-liquid separation, washing, and drying, the U(VI) release rate was measured under acid leaching conditions (pH 5, oscillation rate 120 r / min, leaching time 3 hours). Results are shown below. Figure 15 , Figure 15 The graph shows the removal rate and leaching rate of uranium and other metal ions in the actual uranium-containing wastewater treatment in Example 5. The continuous flow electrochemical mineralization system demonstrated a stable removal effect of U(VI) in the actual uranium-containing wastewater during 24 hours of continuous operation, with an average U(VI) removal rate of 96.6%. The solid-phase mineralization product obtained after 3 hours of operation showed a U(VI) release rate of 9.9% under acid leaching conditions, indicating that the uranium-containing iron silicate mineralization product formed under actual wastewater conditions possesses a certain degree of acid leaching resistance. Simultaneously, this system can also remove some coexisting metal ions, such as Mg. 2+ Ca 2+ Mn 2+ And Al 3+ Al 3+ The removal rate reached 100%, and the release rate was low under acid leaching conditions, indicating that some coexisting metal ions can participate in the iron silicate mineralization process or form a strong bonding environment with the mineralization products, which is beneficial to improving the structural stability of the solid products.
[0060] Comparative Example 1 Uranium-containing simulated wastewater of the same volume and initial U(VI) concentration as in Example 1 was taken, and sodium silicate was added to make the silicate concentration in the system 3 mmol / L (Si). Ferrous salt was added at an amount of iron source equivalent to the amount of anolyte dissolved in Example 1. The reaction conditions were adjusted by adding acid or alkali to keep the pH of the supernatant before solid-liquid separation during precipitation consistent with the pH of the solution after the electrochemical reaction in Example 1 (6.4). After the reaction, the product was subjected to static sedimentation, solid-liquid separation, washing, and vacuum drying to obtain the iron silicate product prepared by the traditional chemical precipitation method, denoted as P-3mMSi. The structure of the obtained product was characterized, and the results showed that the product obtained by this method exhibited a loose amorphous aggregate morphology. Figure 3 No clear and regular lattice fringes were observed in the middle e. Figure 3 The middle f lacks clear crystal diffraction ring characteristics. Figure 2 The presence of only broadened diffraction peaks indicates that its structure has a low degree of order and is mainly composed of amorphous or low-crystallinity iron silicate precipitates. Figure 4 The removal rate of U(VI) by P-3mMSi was 84.3%. The obtained product was subjected to leaching test under simulated acid rain conditions of dilute sulfuric acid with a pH of 5, an oscillation rate of 120 r / min, and a leaching time of 3 h. The uranium leaching rate was 93.6% and the iron release rate was 82.8%. Compared with Example 1, the removal rate of U(VI) by the product obtained by the traditional chemical precipitation method was lower, and the release rates of uranium and iron were significantly increased under acidic leaching conditions, indicating that its fixation stability of uranium was poor. The electrochemical mineralization method of the present invention can significantly improve the structural order and uranium fixation stability of the iron silicate product.
[0061] Comparative Example 2 Similar to Example 1, except that sodium metasilicate was not added, and sodium chloride was added as an electrolyte to make the Cl concentration 3 mmol / L. The resulting sample was denoted as E-0mMSi. The obtained solid product was characterized and its performance was tested. The results are shown in […]. Figure 4 Without the addition of silicates, the main mineral formed was magnetite, with a uranium removal rate of 87.6% and a uranium leaching rate of 42.6% under acid leaching conditions. Compared with the product obtained by adding 3 mmol / L silicates in Example 1, although this comparative example can achieve a certain degree of uranium removal through the formation of iron oxides, the lack of silicate participation prevents the formation of a stable iron-silicate framework and a structural embedding environment for uranium, resulting in a significant decrease in uranium fixation stability. These results indicate that silicates in this invention are not only used to adjust the solution composition but also participate in the construction of the Fe-O-Si framework and uranium mineralization fixation, making them a key factor in reducing uranium leaching rate and improving the long-term stability of uranium-containing solids.
[0062] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for electrochemically synthesizing crystalline iron silicate minerals and simultaneously fixing uranium in wastewater, characterized in that, Includes the following steps: Water-soluble silicates are added to the uranium-containing water body to be treated to obtain a uranium-containing silicate mixture; An electrochemical mineralization reaction was carried out using the uranium-containing silicate mixture as the electrolyte, an iron-containing electrode as the anode, and a conductive inert electrode as the cathode to obtain uranium-containing crystalline iron silicate minerals and treated water. The current density of the electrochemical mineralization reaction is 2~3 mA / cm². 2 ; The concentration of silicon in the uranium-containing silicate mixture is 2-5 mmol / L, calculated as Si. The pH value of the uranium-containing silicate mixture is 2.0~4.
0.
2. The method according to claim 1, characterized in that, The electrochemical mineralization reaction takes 60 to 240 minutes and is carried out at a temperature of 15 to 35°C.
3. The method according to claim 1, characterized in that, The water-soluble silicate includes one or more of sodium silicate, sodium metasilicate, potassium silicate, and potassium metasilicate.
4. The method according to claim 1, characterized in that, The concentration of uranium in the uranium-containing water to be treated is 1~20 mg / L.
5. The method according to claim 1, characterized in that, The iron-containing electrode includes a pure iron electrode, a ferroalloy electrode, or a zero-valent iron-loaded electrode. The pure iron electrode includes one or more of iron plates, iron sheets, iron rods, iron mesh, iron wire, iron filings, and foamed iron. The ferroalloy electrode is made of cast iron or stainless steel. The conductive inert electrode includes a carbon-based electrode, a titanium-based electrode, or a platinum electrode. The carbon-based electrode includes one or more of graphite, carbon rods, carbon felt, carbon cloth, and glassy carbon. The titanium-based electrode includes a titanium plate or titanium mesh. The platinum electrode includes a platinum sheet or platinum mesh.
6. The method according to claim 1 or 5, characterized in that, The distance between the plates of the iron-containing electrode and the conductive inert electrode is 1~15cm.
7. The method according to claim 1 or 2, characterized in that, After the electrochemical mineralization reaction is completed, solid-liquid separation and vacuum drying are performed. The vacuum drying temperature is 50~60℃ and the vacuum degree is -0.1~-0.2MPa.
8. The method according to claim 1 or 4, characterized in that, The uranium-containing water to be treated includes one or more of the following: uranium-containing waste liquid, uranium-containing silicate waste liquid, and uranium-containing mine wastewater.
9. Uranium-containing crystalline iron silicate minerals obtained by the method according to any one of claims 1 to 8.
10. The uranium-containing crystalline iron silicate mineral according to claim 9, characterized in that, The morphology of the uranium-containing crystalline iron silicate minerals includes one or more of the following: layered, chain-like, platy, flocculent, spherical, and microcrystalline aggregates.